Lusiana Profil Sarana Dan Prasarana Cabang Olah Raga Renang di PPLOP Jawa Tengah (Indonesian Journal for Physical Education and Sport, 2021)
The purpose of this study was to determine the condition of adequate infrastructure and the effect of infrastructure conditions on the results of the exercise. The research location in this study was carried out directly with PPLOP Central Java. This study used qualitative research methods. Collecting data using descriptive analysis which is the process of describing research. The variables in this research are the facilities and infrastructure in PPLOP Central Java for swimming sports which include swimming pools, waiting rooms, changing rooms, control rooms, staff rooms and warehouses. The results of the research on swimming pool facilities include a swimming pool track, swimming pool lighting, and swimming pool stairs. Swimming pool infrastructure gets the results of the length of the pool, the depth of the pool, the walls of the pool, and the starting place. Swimming pool supporting facilities and infrastructure include changing rooms and engine rooms. The pool facilities and infrastructure in the swimming pool in Jatidiri are standard because they are in accordance with FINA standards, namely having a track line, the track marking line is straight in front of the Start board, giving numbers from all sides, the number of tracks is 9 and the Start board is the Start board.